Quelques remarques pour vous mettre au parfum à propos du parfum - Czekaj, Anna (Neophilologica, 2017)
The present paper focuses on the problem of automatic translation based on the object-oriented approach proposed by Wiesław Banyś. The author carries out the analysis of the French noun parfum, whose proper translation into Polish may seem too complex from the point of view of automatic translation, as it has many Polish equivalents depending on the context of its use. The paper is an attempt to show how, thanks to the object oriented approach, the problem of choosing an appropriate target language equivalent is solved.